Optimization problems of replacement first or last in reliability theory - Zhao, Xufeng; Nakagawa, Toshio (European journal of operational research, 2012)
► Newly proposed notion of “replacement last” is motivated and analyzed in detail. ► Comparison methods between replacement last and the conventional replacement first are explored. ► Expected cost rate of replacement last in a standard cumulative damage model is obtained and computed. ► Replacement last in maintaining electronic systems of navy ships is applied. This paper takes up age and periodic replacement last models with working cycles, where the unit is replaced before failure at a total operating time T or at a random working cycle Y, whichever occurs last, which is called replacement last. Expected cost rates are formulated, and optimal replacement policies which minimize them are discussed analytically. Comparisons between such a replacement last and the conventional replacement first are made in detail. It is determined theoretically and numerically which policy is better than the other according to the ratios of replacement costs and how the mean time of working cycles affects the comparison results. It is also shown that the unit can be operating for a longer time and avoid unnecessary replacements when replacement last is done. For further studies, expected cost rates of modified models and their applications in a standard cumulative damage model with working cycles are obtained and computed numerically. Finally, case studies on replacement last and first in maintaining electronic systems of naval ships under battle and non-battle statuses are given.